Comparando a saúde no Brasil com os países da OCDE: explorando dados de saúde pública - Lima, Cecília Pessanha (2016)
Healthcare authorities in Brazil produces a large amount of data on health services and use. The appropriate treatment of this data with massive data techniques enables the extraction of important information. This information can contribute to a better understanding of the Brazilian healthcare sector. The evaluation of health systems performance based on the analysis of routinely produced healthcare data has been a worldwide trend. Several countries already maintain monitoring programs based on indicators constructed using this type of data. In this context, the OCDE—Organization for Economic Co-operation and Development, an international organization that evaluates the economic policies of its 34 member countries, has a biennial publication called Health at a Glance, which aims to make the comparison of health systems in OCDE member countries. Although it is not a member country, OCDE seeks to include Brazil in the calculation of some of the indicators, when the data is available, considering that Brazil is one of the largest economies that are still not a member country. This study aims to construct and implement, based on the methodology of Health at a Glance 2015, the calculation in the Brazilian context of 22 indicators in the health field “Use of Health Services.” To develop the set of indicators, first, a wide search of the major national health databases was done to assess data availability. The available data was then extracted using massive data techniques. Those techniques were required because of the large volume of health data in Brazil. The datasets were extracted from three main data sources containing health billing data: SUS, private health insurance and other sources of billing, as public health insurances, DPVAT and private. This work has shown that health data publicly available in Brazil can be used to evaluate the Brazilian health system performance, and include Brazil in the international benchmark of the OCDE countries for the 22 indicators calculated. It can also promote the comparison of the public health sector in Brazil, SUS, and the private health insurance sector based on the same set of indicators. It also made possible the comparison of in each State for SUS, thus underlining the differences in the health-care services among Brazil States for the public sector. The analysis of the indicators showed that, in general, compared to OCDE countries, Brazil has a below-average performance, which indicates a need for efforts to achieve a higher level in the provision of healthcare services that are under these indicators assessment. When separating SUS and private health insurance, the analysis of Brazil’s indicators shows that the private health sector performance is in the average of the OCDE countries. On the other hand, it was observed that SUS was systematically and significantly under the average of the OCDE countries. This highlights the inequalities in healthcare services provision in Brazil between the SUS and private health insurance. The use of the TISS/ANS database as a source of information for the private health insurance sector for the calculation of these indicators will be an improvement over the data available at the time of this analysis. TISS includes all the information exchanged between healthcare services providers and private health insurance operators, in order to perform the payment of healthcare services provided.